Bioactive Enrichment and Sustainable Processing of Vegetable Oils: New Frontiers in Agri-Food Technology - Sandra Montoro-Alonso; Xavier Expósito-Almellón; Daniel Martínez-Baena; Joana Martínez-Martí; Ascensión Rueda-Robles; Raúl Pérez-Gálvez; Rosa Quirantes-Piné; Jesús Lozano-Sánchez (Foods)
Vegetable oils are highly valued for their nutritional and functional properties, driving scientific interest in developing innovative technologies to enhance production processes. These advancements aim to improve yield, nutritional profiles and organoleptic and functional characteristics. Additionally, vegetable oils have been recognised for their ability to incorporate phenolics as bioactive compounds through stabilisation methods, further enhancing their health benefits. This study conducts a systematic review addressing two main objectives: (i) advanced technologies intended to enhance extraction efficiency while improving the overall quality of vegetable oils and (ii) stabilisation strategies developed to enrich and fortify edible vegetable oils with special focus on phenolic compounds. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology was applied to evaluate their applications in developing bioactive vegetable oil ingredients and foods. Extraction techniques were assessed based on efficiency in yield and their impact on nutritional, organoleptic and functional properties. Pulsed electric field technology emerged as the most promising approach, offering an optimal balance between oil yield and quality. Combining stirring or high-performance dispersion with ultrasound proved effective in forming stable emulsions for phenolic stabilisation. These strategies provide valuable insights for the agro-industrial sector to enhance production processes and develop healthier, bioactive vegetable oils.